The Influence Of Administrative Service Quality And Campus Infrastructure On Student Satisfaction: The Role Of Student Loyalty As A Mediator - Cornelia Derry Chandradara; Suhana Suhana (UNIVED Press, 2025)
Higher education in Indonesia is expanding, but challenges in administrative services and infrastructure affect student satisfaction and loyalty. Politeknik Bumi Akpelni faces significant gaps, with 65% of students dissatisfied with services and 58% with facilities. This study uses primary data from questionnaires and secondary data, with a sample of 499 final-year students selected purposively. Data analysis includes validity and reliability tests, multiple linear regression, F-test, R², t-tests, and Sobel test for mediation analysis on student loyalty. Addressing these issues is crucial to improving student loyalty and the institution’s reputation. Administrative Service Quality has a positive and significant effect on Student Loyalty. Campus Infrastructure has a positive and significant effect on Student Loyalty. Administrative Service Quality has a positive and significant effect on Student Satisfaction. Campus Infrastructure does not have an effect on Student Satisfaction. Student Loyalty has a positive and significant effect on Student Satisfaction. There is a mediating effect of Student Loyalty in mediating the relationship between Administrative Service Quality and Student Satisfaction. There is a mediating effect of Student Loyalty in mediating the relationship between Campus Infrastructure and Student Satisfaction.